The Effect of Work Stress, Workload, and Work Environment on Turnover Intention in the Production Division of PT Wijaya Gyokai Indonesia - Hermawan, Hilman; Hartono, Edy (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2026)
This study aims to analyze the effects of work stress, workload, and work environment on turnover intention among employees in the production division of PT Wijaya Gyokai Indonesia. A quantitative approach was employed using survey data collected from 120 employees selected from a population of 170 through Slovin’s formula with a 5% margin of error. Data were gathered using a Likert-scale questionnaire and analyzed through multiple linear regression with SPSS. The results show that work stress (β = 0.230; p < 0.05) and workload (β = 0.353; p < 0.05) have a positive and significant effect on turnover intention, while work environment (β = -0.330; p < 0.05) has a negative and significant effect. Concurrently, these factors have a large impact on turnover intention; an Adjusted R Square value of 0.631 shows that work stress, workload, and work environment account for 63.1% of turnover intention. These results imply that enhancing the workplace and controlling employee stress and workload are crucial tactics to lower turnover intention in manufacturing firms.